On the case : explorations in social history - Iacovetta, Franca, 1957-; Mitchinson, Wendy (Toronto ; Buffalo : University of Toronto Press, 1998)
"On the Case is a timely book intended to provide a forum for discussing the theoretical and methodological issues that arise in connection with the use of case files in research. The book brings together theoretical debates, new research, and new research methods and offers compelling illustrations of the drama, conflict, and power relations that the case file can capture." "This collection of essays features some of Canada's leading social historians. Readers will encounter an impressive array of case files, including psychiatrists' accounts of sexual deviants, employment records of sailors, state welfare and Indian Affairs reports, court records, the patient forms of hospital and asylum doctors, and state security files. While the contributors differ in choice of subject and approach, they share a commitment to the progressive traditions of social history. They recover the voices and actions of people - not only of those with power but also of those who seemingly have none."--Jacket.
""15 The 'Grab Bag' Mennonite Refugee Family in Post-War Canada""""Afterword: Telling Stories about Dead People""; ""CONTRIBUTORS""
Print version record.
Includes bibliographical references.
English.
JSTOR
Keywords: Historical sociology -- Methodology; Canada -- Social conditions -- Research; Records -- Canada; Canada -- Conditions sociales -- Recherche; Sociologie historique -- Méthodologie.; Archives -- Canada; SOCIAL SCIENCE -- Anthropology -- General; SOCIAL SCIENCE -- Regional Studies; SOCIAL SCIENCE -- Sociology -- General; HISTORY -- General; Historical sociology -- Methodology; Social history -- Research; Canada; Records; Quellenforschung; Sozialgeschichtsschreibung; Aufsatzsammlung; Kanada; Akte; Sociale geschiedenis (wetenschap); Sociologie historique -- Méthodologie.; Archives -- Canada; Canada -- Conditions sociales -- Recherche; Electronic books; e-books.; Records (Sports); Livres numériques.